Trust in government, tax digitalization and tax education influence tax compliance with experience as a moderation - Haq, Faizal Akhsan; Tarmidi, Deden (Educoretax, 2024)
This study aims to examine the effect of trust in the government, tax digitization, and tax education on tax compliance with experience as a moderating variable. This study is an associative quantitative research using primary data in the form of a questionnaire. The population in this study is individual taxpayers registered at KPP Pratama Cilacap by giving several statements or questions to respondend totaling 97,483 people and a sample of 398 people. This research uses purposive sampling based on Slovin theory. The data analysis technique used in this study is the PLS-SEM model. This study uses descriptive statistical tests, measurement evaluation models, structural evaluation models and goodness-of-fit evaluation models. This study concludes that trust in government, tax digitalization, tax education and experience give positive impact to tax compliance. Experience cannot moderate the impact of trust in government to tax compliance. Experience weakened the impact of tax digitalization to tax compliance. Experience can moderate the impact of tax education on tax compliance.